Outbreak of Meningitis in Iraq in 2023 - Khalid Hama Salih MBChB, DCH, FIBMS-ped; Zana Baqi Najmadden MBChB, CABP; Bahadin Qader Ahmed MBChB, FKBMS; Pishdar Abdullah Ismael MBChB, FKBMS; Kaiwan H. Kareem MBChB; Lana Diyar Abdulqadir MBChB; Roza M. Sabir MBChB; Basta J. Abdalla MBChB; Binay A. Qadir MBChB; Razhan M. Mohammed MBChB; Ali Salih karim MBChB (SAGE Publishing, 2024)
Objective . To determine clinical presentations and laboratory findings of meningitis outbreak among children in 2023 in Iraq. Method . the demographic data (gender, age, symptoms, and disease transmission among family members) were collected from child patients, who were admitted to Halabja and Sulaimania pediatric teaching hospital in the period of 15 March 2023 to 1st of August, 2023. The blood and cerebrospinal fluid (CSF) specimens were collected for hematological, biochemical, microscopic, and microbiological examinations, including culturing and FilmArray meningitis/encephalitis panel. Results . The population studied were 170 children between 1 and 18 years old, Males were 110 (64.7%), and females were 60 (35.3%). Children between 5 and 10 years old had the highest frequency, whereas only 2 children were <1 year. Clinical symptoms were fever in 100%, followed by headache, vomiting, convulsion, photophobia, and lethargy (79%, 12%, 3%, 3%, 2%) respectively. CSF parameters were: 38.8% of them had >1000 leucocytes/µ, followed by 31.2% for those who had <300 cells/µ, differential CSF leucocytes, 82.4% were monocytes, and sugar was normal at 84.1%. while protein was <40 mg/d in 55.9% of them. Conclusion . Meningitis outbreak due to enterovirus was recorded, and age predilection and clinical presentation refer to different serotypes. Further work is needed to define the species and serotypes of the virus and define the environmental source of the virus.